Pengaruh Bundilng Produk pada keputusan Impulsif terhadap Pembelia Mie Gacoan di Karawang - Nadira Aisha Amidia; Nurmala Dewi Rahmawati; Abdul Yusuf (Masyarakat Ekonomi Syariah Bogor, 2024)
The aim of the research is to analyze the effect of product bundling on impulsive decisions in purchasing Mie Gacoan in Karawang. By using quantitative methods, it is hoped that it can provide a comprehensive picture of the influence of product bundling on impulsive decisions in purchasing Mie Gacoan in Karawang. The results of this research can be a reference for Mie Gacoan and other business people in developing innovative and effective marketing strategies. Based on research that has been conducted by researchers, it can be concluded that product bundling has an influence on impulsive decisions to purchase gacoan noodles in Karawang. Only 24.4% and the rest is influenced by other factors which were not thoroughly examined in this research. Therefore, it can be concluded that product bundling has a positive and large influence on impulsive decisions. Keywords: product bundling, impulsive decisions